VD_FINDINFO Décision / 2017 / 434 vom 14. Juni 2017 - VD Tribunal cantonal (2017)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉCUSATION, CONSULTATION DU DOSSIER | 101 al. 1 CPP (CH), 107 CPP (CH), 221 al. 1 let. c CPP (CH), 56 let. f CPP (CH)